Removal of Toxic Heavy Metals Using Genetically Engineered Microbes: Molecular Tools, Risk Assessment, and Management Strategies: Penghapusan Logam Berat Beracun Menggunakan Mikroba Hasil Rekayasa Genetika: Alat Molekuler, Penilaian Risiko, dan Strategi Manajemen - Muslim, Ola Abdulwahhab; Bakr, Hayder Mohammed; Jwaziri, Abdulhussain Kadhim; Ali, Kawther Mohammed Radah (Academia Open, 2024)
Background: The growing occurrence of heavy metal pollutants in many environmental sources requires effective methods for treatment. Genetically engineered microorganisms, namely bacteria such as Shewanella oneidensis and Cupriavidus metallidurans, have been highly useful for the specific removal of heavy metals. Purpose: This study aims to examine the effectiveness of genetically modified Shewanella oneidensis and Cupriavidus metallidurans, obtained from MB Genetics, in removing harmful heavy metals from various environmental sources. Methods: Genetically modified strains were obtained from MB Genetics, a company specializing in the creation of transgenic microbes. Shewanella oneidensis and Cupriavidus metallidurans were utilized to mitigate the presence of harmful heavy metals in water under different pH levels. Results: The study showed a notable effectiveness, as both bacterial strains successfully eliminated 91% of Lead at pH 7. The study highlighted the substantial impact of pH on the levels of heavy metals in the environment. Conclusion: The need to eradicate harmful heavy metals in the present time can be efficiently tackled by using genetically modified bacteria. Shewanella oneidensis and Cupriavidus metallidurans demonstrated remarkable efficacy in the removal of heavy metals. Highlights: Modified bacteria remove 91% of lead at neutral pH. CRISPR/Cas9 enhances bacteria for efficient heavy metal removal. pH optimization is key for effective heavy metal absorption. Keywords: Toxic heavy metals, Pseudomonas aeruginosa, Shewanella oneidensis, Cupriavidus metallidurans